Penggunaan Sistem Hidroponik sebagai Alternatif Optimalisasi Budidaya Sayuran Organik: Studi Kasus Desa Tanjung Hutan - Zulgani; Hastuti, Dwi; Junaidi; Parmadi; Rafiqi; Hardiani (WIDA Publishing, 2023)
This article aims to introduce and promote hydroponics as an alternative for optimizing organic vegetable cultivation. The hydroponic use has several objectives, namely: 1) Achieving optimal growth and harvest results for organic vegetables, 2) Advocating hydroponics as an alternative method for cultivating organic vegetables with effective and environmentally friendly pest and disease control techniques, 3) Developing efficient water and energy management techniques, such as implementing water recycling systems and energy-saving technologies, 4) Establishing empowerment programs that provide knowledge and skills related to organic hydroponic cultivation, covering technical, managerial, and sustainability aspects. With the implementation of hydroponic empowerment, it is expected that the community in Tanjung Hutan Village can increase the availability of organic vegetables, reduce dependency on synthetic chemicals, and provide economic benefits through job opportunities and new enterprises. Furthermore, optimizing organic vegetable cultivation holds significant potential in meeting the demand for high-quality and sustainable organic food.